2005
DOI: 10.1093/ndt/gfh658
|View full text |Cite
|
Sign up to set email alerts
|

Long-term renal safety of tenofovir disoproxil fumarate in antiretroviral-naive HIV-1-infected patients. Data from a double-blind randomized active-controlled multicentre study

Abstract: Through 144 weeks, TDF and stavudine, each administered in combination with efavirenz and lamivudine, had similar renal safety profiles in treatment-naive HIV-infected patients with normal renal function at baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
100
2
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(109 citation statements)
references
References 16 publications
5
100
2
2
Order By: Relevance
“…Tenofovir may have contributed to ATN in three additional patients presenting with septic shock (two patients) and in conjunction with metformin (one patient), because they all displayed proximal tubular dysfunction. Tenofovir has gained widespread use for the treatment of HIV-1 and hepatitis B infections on the basis of its efficacy and tolerability (21)(22)(23)(24). Phase III studies showed excellent renal safety, but cases of tenofovirrelated nephrotoxicity were first reported in 2002 (12,25).…”
Section: Discussionmentioning
confidence: 99%
“…Tenofovir may have contributed to ATN in three additional patients presenting with septic shock (two patients) and in conjunction with metformin (one patient), because they all displayed proximal tubular dysfunction. Tenofovir has gained widespread use for the treatment of HIV-1 and hepatitis B infections on the basis of its efficacy and tolerability (21)(22)(23)(24). Phase III studies showed excellent renal safety, but cases of tenofovirrelated nephrotoxicity were first reported in 2002 (12,25).…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of the relationship between renal function and antiretrovirals have been on the basis of small or moderate patient groups and have tended to focus exclusively on tenofovir (16,21,22,25,27,28). In EuroSIDA, 4474 patients were analyzed, and many antiretrovirals were investigated as being associated with chronic renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of its tolerability, convenient dosing and efficacy, this nucleoside reverse transcriptase inhibitor (NRTI) has been widely used as a component of cART regimens. There are contradictory data on tenofovir-related damage: from documented damage in early reports [24][25][26][27] to a marked lack of renal toxicity in randomized placebo-controlled trials [28][29][30][31]; moreover, toxicity was found to be increased when tenofovir was given with ritonavir-boosted protease inhibitors (PI/r) compared with tenofovir given with nonnucleoside reverse transcriptase inhibitors (NNRTIs) or cART that did not include tenofovir [32]. A mechanism involving an interaction between tenofovir and PIs/r resulting in an increased risk of renal damage has been suggested [33].…”
Section: Discussionmentioning
confidence: 99%